INNOVATIVE TECHNOLOGIES IN THE DIAGNOSIS AND TREATMENT OF INFERTILITY: A COMPREHENSIVE REVIEW - Zuzanna Dobrakowska,; Marzena Swojnóg,; Radosław Swędrak,; Jakub Klepacz, (International Journal of Innovative Technologies in Social Science, 2026)
Infertility is increasingly recognized as a condition affecting diverse populations and one that requires advanced medical and technological approaches to support effective diagnosis and treatment. In recent years, significant progress in medical sciences and digital technologies has refined the ways infertility is assessed and managed. Contemporary diagnostic methods now include high-resolution imaging, hormonal and genetic testing, microbiome evaluation, and immunological analysis. These advancements enable clinicians to identify reproductive disorders with greater precision.Artificial intelligence (AI) and robotic systems further support clinical decision-making by improving embryo selection, predicting treatment outcomes, and standardizing laboratory procedures. Advances in assisted reproductive technologies (ART) have expanded therapeutic options for patients who previously had limited chances of achieving pregnancy.Although technology plays a crucial role in modern infertility care, patient experiences and psychological well-being remain equally important, as treatment can be both emotionally and physically demanding. This review summarizes current knowledge on innovative technologies used in the diagnosis and treatment of infertility and highlights how the continued development of these methods enhances clinical outcomes and patient care.